Musical Practice in Music Students During COVID-19 Lockdown - Nusseck, Manfred; Spahn, Claudia (Frontiers in Psychology, 2021)
The pandemic situation has forced students in higher education to use alternative learning routines due to reduced activities at universities and educational facilities. Especially music students needed to adapt their musical learning to this particular situation. Mostly affected by the lockdown was the musical practicing behaviour, especially when practicing at the University of Music was not possible. In this study, music students in their second and third semester were asked to provide information on their practicing situations during the COVID-19 lockdown. They were required to fill in questionnaires about the practicing time and concepts of self-efficacy and self-regulation for musical learning. The data of 18 music students were collected. For the analysis, they were compared with the answers of 15 music students who were asked the same questions half a year earlier before the pandemic situation occurred. The results showed that the music students relocated mostly to their parents’ homes for practicing during the lockdown. In the amount of practicing, the Bachelor of Music students practiced less during lockdown compared to before the lockdown. The mean self-efficacy for musical learning did not differ between before and during the lockdown. For the self-regulated musical learning, the music students showed significantly higher values in the subscale on reflecting and creating a framework for the progress of musical learning during the lockdown. The findings indicate that the music students developed certain self-regulated learning skills during the lockdown and managed to find suitable solutions in continuing with their musical learning without reservation.